The Analysis of Typology Klaassen on Deposits and Credits at Regional Development Banks in Java and Bali - Mala, Chajar Matari Fath; Jumono, Sapto (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
The purpose of this study is to examine RDB (Regional Development Bank) performance in 6 provinces: Bali, DKI Jakarta, West Java and Banten, Central Java, East Java, and Yogyakarta from 2012 to 2022 using the Klaassen  Typology for evaluating banks by credit-to-deposit ratios and growth against provincial averages. Although regional development banks (RDBs) are crucial for regional economic development, previous studies have not provided a comparative framework to understand the disparity of credit and deposit growth between RDBs in different provinces. The result shows strong credit growth of Bank Bali without consistent, good credit management in Bank DKI while the deposits are not managed well, then Bank Jabar-Banten, which maintained the market share but lack of deposit strategy, while Bank Jateng still outperformed in most provincial growth, albeit at times, the growth is fluctuant, happened to Bank Jatim that shows inconsistent performance only to recover in recent years, and Bank DIY still achieved strong credit while poor in deposit. This study also suggests expanding the lending portfolios, looking for niche market opportunities, adopting financial technology, and having better credit distribution employments in line with regional economic growth along with better consumer education programs to improve the RDB performance. The results also help fill a research gap in structured performance evaluation for RDBs, and they help elucidate the need for tailored banking strategies that effectively sustain financial stability at the regional level.